Essentials of clinical infectious diseases [ - Wright, William F. (Demos Medical, 2013)
This quick-reference handbook on clinical infectious diseases is intended for a broad medical audience. Written in outline format with 45 short focused chapters covering core infectious disease topics, the book provides a basic introduction to identifying and managing commonly encountered problems. Organized by system, each section begins with a general framework covering clinical presentation, laboratory and diagnostic evaluation, and empirical antibiotic therapy. Individual chapters within sections are devoted to particular problems and cover pathogenesis and risk factors, microbial causes